Causal effects and metabolites mediators between immune cell and risk of colorectal cancer: a Mendelian randomization study - Yang, Qian; Duan, Bixia; Yue, Jian; Zhang, Donglin; Chen, Xueping; Shi, Mengjia; Kan, Jie; Li, Ruochan; Li, Hongda; Gan, Lin (Frontiers in Immunology, 2024)
Abstract Objective: The involvement of immune cells in colorectal cancer (CRC) and their interplay with metabolic disorders are yet to be fully elucidated. This study examines how peripheral immune cells, inferred genetically, affect CRC and investigates the intermediary roles of metabolites. Methods: We employed a two-sample bidirectional Mendelian randomization (MR) approach to assess the causal influence of immune cells on CRC. Additionally, a two-step MR strategy was utilized to pinpoint potential metabolites that mediate this effect. Our analysis incorporated data from genome-wide association studies (GWAS), involving 731 immune cell types, 1,400 metabolites, and CRC outcomes. The primary method of analysis was randomized inverse variance weighting (IVW), supported by MR-Egger, weighted median, simple mode, and weighted mode analyses. Sensitivity checks were conducted using Cochran’s Q test, MR-PRESSO test, MR-Egger regression intercept, and leave-one-out analysis. Results: The study identified 23 immune cell types and 17 metabolites that are causally linked to CRC. Our mediation analysis highlighted that nine metabolites act as intermediaries in the relationship between nine specific immune cells and CRC risk. Notably, The ratios of Adenosine 5'-monophosphate (AMP) to aspartate and Retinol (Vitamin A) to linoleoyl-arachidonoyl-glycerol (18:2 to 20:4) were found to concurrently mediate the promoting effects of Myeloid DC %DC and BAFF-R on B cells in colorectal cancer (CRC). Moreover, iminodiacetate (IDA) was found to mediate the protective effect of CD14+ CD16- monocytes on CRC, contributing 11.8% to this mediation. In contrast, IDA was also seen to decrease the protective effect of IgD+ CD38br %B cells on CRC risk, with a mediation effect proportion of -10.4%. Conclusion: This study delineates a complex network involving immune cells, metabolites, and CRC, suggesting a multifaceted pathophysiological interaction. The identified causal links and mediation pathways underscore potential therapeutic targets, providing a foundation for interventions aimed at modulating immune responses to manage CRC.